ELECTRO-DEGRADATION OF REACTIVE BLUE DYES USING CYLINDER MODIFIED ELECTRODE: Ti/β-PbO2 AS DIMENSIONALLY STABLE ANODE - Aris Mukimin; Karna Wijaya; Agus Kuncaka (Universitas Gadjah Mada, 2010)
A cylinder modified electrode of the β-PbO2 was fabricated by anodic electro-deposition method on titanium substrate. The PbO2 layer prepared from high acid solution (pH: 0.3) that contains a mixed of 0.5 M Pb(NO3)2, 1 M HNO3, and 0,02 M NaF. The physicochemical properties of the PbO2 electrode were analyzed by using Energy Dispersive X-Ray Analysis and X-Ray Diffraction. The analyses have shown that oxide layer has an O/Pb ratio about 1.6 and the PbO impurities are formed in the surface layer besides the β-PbO2. The modified electrode was used as anode paired stainless cathode in the electro-degradation of reactive blue dye. The results of the electro-catalytic oxidation process of the dye solution were expressed in terms of the remaining intensity dye and chemical oxygen demand (COD) values. The modified electrode has removal efficiency of the reactive blue dye at voltage of 7 V, pH of 7, concentration NaCl of 2 g/L, initial dye concentration of 100 mg/L with simple and short time operations.